Drug review: Carfilzomib - Prasanth Ganesan (Indian Journal of Medical and Paediatric Oncology)
Carfilzomib is a second generation proteasome inhibitor approved for use in relapsed/ refractory multiple myeloma. The mechanism of action, usage, toxicity and key trials involving this agent are briefly reviewed here.